PARTISIPASI MASYARAKAT PADA PEMBANGUNAN INFRASTRUKTUR DRAINASE DI DESA MAKALU KECAMATAN POSUMAEN KABUPATEN MINAHASA TENGGARA (The Community Participation in Drainage Development in Makalu Village, Pusomaen District, Southeast Minahasa Regency) - Colin Maringka; Charles R. Ngangi; Vicky R. B. Moniaga (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this study was to determine the community participation in drainage development in Makalu Village, Pusomaen District, Southeast Minahasa Regency. The selection of respondents was done by using purposive sampling method. The data collected is in the form of primary data and secondary data. The results showed that the level of community participation at the planning stage was 64.16%, and the participation rate at the implementation stage in the form of thoughts, skills, goods and money was 88.6%, and the participation rate at the evaluation stage was 86.5%.Keywords: Community Participation